Student Perceptions of College Faculty Who Use OER - Vojtech, Gabrielle; Grissett, Judy (International Review of Research in Open and Distributed Learning, 2017)
Research indicates that students find open educational resources (OER) favorable, but there is no research regarding students’ perceptions of faculty who use open textbooks. In the present study we examined this topic experimentally with two undergraduate psychology courses at a small public university. Participants read two passages—one about an instructor using an open textbook and another using a traditional copyrighted textbook—and rated each instructor on a range of characteristics through closed- and open-ended questions. Participants rated faculty using an open textbook higher on kindness, encouragement, and creativity than faculty using a traditional copyrighted textbook, and were more likely to want to take a class with faculty using an open textbook. Participants frequently mentioned textbook cost in their justifications.